In Silico Approaches for Some Sulfa Drugs as Eco-Friendly Corrosion Inhibitors of Iron in Aqueous Medium - Soukaina Alaoui Mrani; Nadia Arrousse; Rajesh Haldhar; Abdellatif Ait Lahcen; Aziz Amine; Taoufiq Saffaj; Seong-Cheol Kim; Mustapha Taleb (Lubricants, 2022)
This paper addresses the prediction of the adsorption behavior as well as the inhibition capacity of non-toxic sulfonamide-based molecules, also called sulfa drugs, on the surface of mild steel. The study of the electronic structure was investigated through quantum chemical calculations using the density functional theory method (DFT) and the direct interaction of inhibitors with the iron (Fe) metal surface was predicted using the multiple probability Monte Carlo simulations (MC). Then, the examination of the solubility and the environmental toxicity was confirmed using a chemical database modeling environment website. It was shown that the presence of substituents containing heteroatoms able to release electrons consequently increased the electron density in the lowest unoccupied and highest occupied molecular orbitals (LUMO and HOMO), which allowed a good interaction between the inhibitors and the steel surface. The high values of EHOMO imply an ability to donate electrons while the low values of ELUMO are related to the ability to accept electrons thus allowing good adsorption of the inhibitor molecules on the steel surface. Molecular dynamics simulations revealed that all sulfonamide molecules adsorb flat on the metal surface conforming to the highly protective Fe (1 1 0) surface. The results obtained from the quantum chemistry and molecular dynamics studies are consistent and reveal that the order of effectiveness of the sulfonamide compounds is P7 > P5 > P6 > P1 > P2 > P3 > P4.